Advanced glycation end product carboxymethyl-lysine and risk of incident peripheral artery disease in older adults: The Cardiovascular Health Study. (September 2019) - Garg, Parveen K; Biggs, Mary L; Barzilay, Joshua; Djousse, Luc; Hirsch, Calvin; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Mukamal, Kenneth J
Carboxymethyl-lysine is an advanced glycation end product that is detectable in the serum. Higher carboxymethyl-lysine levels have been associated with increased risk of coronary heart disease, stroke and cardiovascular mortality. We determined whether high carboxymethyl-lysine levels are also associated with the risk of peripheral artery disease in Cardiovascular Health Study participants who were all aged 65 years and older at baseline. Multivariate Cox proportional hazards models were used to determine the association of baseline carboxymethyl-lysine levels with incident peripheral artery disease in 3267 individuals followed for a median length of 10.0 years. A total of 157 cases of incident peripheral artery disease occurred during follow-up. No significant relationship between carboxymethyl-lysine and risk of peripheral artery disease was found (hazard ratio per standard deviation increment = 1.03; 95% confidence interval = 0.87, 1.23).